Impact of Oral Metronidazole, Vancomycin, and Fidaxomicin on Host Shedding and Environmental Contamination With Clostridioides difficile. (21st May 2021) - Turner, Nicholas A; Warren, Bobby G; Gergen-Teague, Maria F; Addison, Rachel M; Addison, Bechtler; Rutala, William A; Weber, David J; Sexton, Daniel J; Anderson, Deverick J
Abstract: Background: Shedding of Clostridioides difficile spores from infected individuals contaminates the hospital environment and contributes to infection transmission. We assessed whether antibiotic selection affects C. difficile shedding and contamination of the hospital environment. Methods: In this prospective, unblinded, randomized controlled trial of hospitalized adults with C. difficile infection, patients were randomized 1:1:1 to receive fidaxomicin, oral vancomycin, or metronidazole. The primary outcome was change in environmental contamination rate during treatment. Secondary outcomes included stool shedding, total burden of contamination, and molecular relatedness of stool versus environmental C. difficile isolates. Results: Of 33 patients enrolled, 31 (94%) completed the study. Fidaxomicin (−0.36 log10 colony-forming units [CFUs]/d [95% confidence interval (CI), −.52 to −.19]; P < .01) and vancomycin (−0.17 log10 CFUs/d [−.34 to −.01]; P = .05) were associated with more rapid decline in C. difficile shedding than metronidazole (−0.01 log10 CFUs/d [95% CI, −.10 to .08). Both vancomycin (6.3% [95% CI, 4.7–8.3) and fidaxomicin (13.1% [10.7–15.9]) were associated with lower rates of environmental contamination than metronidazole (21.4% [18.0–25.2]). With specific modeling of within-subject change over time, fidaxomicin (adjusted odds ratio, 0.83 [95% CI, .70–.99]; P = .04) was associated with more rapid decline in environmental contamination than vancomycin or metronidazole. Overall, 207 of 233 environmental C. difficile isolates (88.8%) matched patient stool isolates by ribotyping, without significant difference by treatment. Conclusions: Fidaxomicin, and to a lesser extent vancomycin, reduces C. difficile shedding and contamination of the hospital environment relative to metronidazole. Treatment choice may play a role in reducing healthcare-associated C. difficile transmission. Clinical Trials Registration: NCT02057198. Abstract : Fidaxomicin and vancomycin reduce Clostridioides difficile shedding and environmental contamination relative to metronidazole. Reducing transmission through environmental contamination may be another consideration in selection of C. difficile treatment.